Preparation method of nano-reinforced titanium-based composite material

By adding nano-scale reinforced phases to the TC4 titanium alloy powder, using ball milling, tableting and sintering processes, the problems of low hardness and poor wear resistance of TC4 titanium alloy are solved, and its hardness and wear resistance are significantly improved.

CN119843093APending Publication Date: 2025-04-18ANSTEEL BEIJING RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510028819.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

TC4 titanium alloy has low hardness and poor friction and wear resistance, which limits its application in special environments.

Method used

Add nanoscale graphene, carbon nanotubes, boron carbide, and silicon carbide particles to the micron-scale TC4 titanium alloy powder to improve the hardness of the composite material through ball milling, tableting and sintering processes.

Benefits of technology

It significantly improves the hardness of TC4 titanium alloy, up to 4000HV, improves its wear resistance and expands its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843093A_ABST
    Figure CN119843093A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a nano reinforced titanium-based composite material, TC4 titanium alloy powder is selected as a base material, and the average particle size is 60-150 [mu] m; the reinforcing phase is selected from nanoscale graphene, carbon nanotubes, boron carbide nanoparticles and silicon carbide nanoparticles; the method comprises the following steps: 1) uniformly mixing materials together by using a ball mill, wherein the mass fraction of nano particles in the mixture is 0.2-2.0 wt%; (2) the mixed powder obtained in the step (1) is coagulated into a cluster by using epoxy resin and white latex as adhesives, then the cluster is placed in a tool steel grinding tool of a tablet press, and tabletting of the composite material is completed through the steps of filling, pressing forming, pressure maintaining and demolding; and (3) sintering the tablets obtained in the step (2) by using an argon protection box type atmosphere furnace. The nanoscale graphene, the carbon nanotubes, the boron carbide or the silicon carbide particles are added into the micron-sized TC4 titanium alloy powder, so that the hardness of the TC4 titanium alloy can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of vanadium and titanium, and in particular relates to a method for preparing a nano-enhanced titanium-based composite material. Background Art

[0002] The density of titanium alloy is 4.51g / cm 3 , less than 60% of the density of steel, high specific strength, non-magnetic, good sound transmission, impact resistance, excellent corrosion resistance in most acid, alkali and salt solutions, and extremely superior corrosion resistance to seawater, especially polluted seawater. In recent years, it has been called marine metal and is widely used in the marine field.

[0003] TC4 titanium alloy is the most widely used alloy among titanium alloys. It is a universal titanium alloy that has good mechanical properties, excellent fatigue resistance and crack growth resistance, excellent corrosion resistance, excellent comprehensive performance and good processing characteristics not only at room temperature but also at high temperature. However, the hardness of TC4 titanium alloy is lower than that of common materials such as steel (TC4 hardness generally does not exceed 350HV), and its poor friction and wear resistance restricts the use of TC4 titanium alloy in some special environments, especially in pipelines, valves and accessories, propellers and propeller shafts in power drive devices, and propellers. Improving the hardness and wear resistance of titanium alloy can better expand the scope of application of titanium alloy.

[0004] Adding reinforcement phase can improve the hardness and wear resistance of titanium alloy. When selecting reinforcement phase, attention should be paid not only to the thermal expansion coefficient matching with the titanium matrix, but also to ensure the compatibility of the interface, not to chemically react with the matrix, and to ensure that the reinforcement phase is evenly distributed and not agglomerated. At present, there are two types of reinforcement phases, namely fiber reinforcement phase and particle reinforcement phase.

[0005] For the fiber reinforcement phase, titanium alloys are prone to react with most toughening fibers at high temperatures to generate interface products, which affects the performance of the material. Therefore, the selected fiber reinforcement cannot be a fusible material. The available fiber reinforcements mainly include ceramic fibers such as silicon carbide and Al2O3, as well as refractory metal fibers such as W, Mo, Ti, and Nb. Therefore, the requirements for the process are strict and complex. Xi Shaojing et al. used PAN-based carbon fibers and titanium powder as raw materials to study composite materials with different carbon fiber forms. The experimental results show that after nickel plating of carbon fibers, the bonding effect between the fibers and titanium alloys is improved, and the gap defects are reduced. Xiao Zhiyuan et al. used Raman spectroscopy to study the organizational evolution of the prepared silicon carbide fibers and pyrolytic carbon coatings. The experimental results show that after a certain period of vacuum heat exposure, reaction products of different shapes and sizes appear in the matrix of silicon carbide f / C / Mo / Ti-6Al-4V composite materials, mainly TiCx and Ti3AlC2.

[0006] Compared with fiber reinforced phase, particle reinforced phase has the advantages of simple preparation process and easier realization. Other advantages of particle reinforced phase are that its material properties are less sensitive to the mismatch of thermal expansion coefficients between the reinforcement phase and the matrix, and can also significantly reduce the cost of materials. Silicon carbide, TiC, boron carbide, Ti2B, TiB and ZrB2 are the more ideal particle reinforced phases found so far. S. Gorsse et al. compared the chemical stability and mechanical compatibility of the reinforcement phase with titanium alloy. The results showed that the order of hardness is TiB>CrB>boron carbide>silicon carbide>Ti5Si3 (from large to small); the order of chemical stability combined with titanium alloy is TiB>Ti5Si3>CrB>boron carbide>silicon carbide (from large to small). Summary of the invention

[0007] The invention provides a method for preparing a nano-reinforced titanium-based composite material. The hardness of the TC4 titanium alloy can be effectively improved by adding nano-graphene, carbon nanotubes, boron carbide and silicon carbide particles into micron-sized TC4 titanium alloy powder.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions:

[0009] A method for preparing a nano-reinforced titanium-based composite material, wherein the base material is TC4 titanium alloy powder with an average particle size of 60 to 150 μm; the reinforcing phase is one of nano-graphene, carbon nanotubes, boron carbide nanoparticles, and silicon carbide nanoparticles;

[0010] The preparation method comprises the following steps:

[0011] 1) Using a ball mill to uniformly mix the experimental materials, the mass fraction of the nanoparticles in the mixture is 0.2-2.0 wt%;

[0012] 2) using epoxy resin and latex glue as adhesives to agglomerate the mixed powder obtained in step 1) into a mass, and then placing the mass in a tool steel mold of a tablet press, and completing the tableting of the composite material through the steps of filling-pressing-pressing-holding-demolding;

[0013] 3) Sintering the pressed tablet obtained in step 2) in an argon-protected box-type atmosphere furnace.

[0014] The ball mill has an orbital speed of 100 to 300 r / min, a rotational speed of 300 to 600 r / min, a frequency of 30 to 50 Hz, a required time of 15 to 30 minutes, and a unidirectional operation mode.

[0015] The tableting parameters are as follows: the maximum pressure borne by the mold is 50-450 MPa, and the holding time is 10-60 s;

[0016] The mass of the tablet sample is 6-70 g, the shape of the tablet sample is a disc, the diameter is 20-50 mm, and the thickness is 5-50 mm.

[0017] The sintering parameters are as follows: the sintering heating method is heating with the furnace, and the average heating rate is 5-20°C / min; the sintering temperature is selected to be 1000-1450°C; and the sintering cooling method is furnace cooling.

[0018] The mechanism by which the nano-reinforced phase improves the hardness of the composite material in the present invention is as follows:

[0019] As the content of graphene nano-reinforced phase changes, the hardness value of TC4 / graphene composite material changes. Among them, the average hardness of TC4 titanium alloy mixed with 1% graphene is the lowest; the average hardness of the sample mixed with 2% graphene is the highest. It shows that adding a small amount of graphene has a significant effect on the hardness of TC4. The reason for the increase in hardness is that the graphene is embedded in the matrix, which changes the lattice constant of the surrounding matrix. In addition, some TiC is generated, which hinders the movement of dislocations together with graphene, so that a large number of dislocations are accumulated in the parts where they contact each other, thereby increasing its hardness. When the graphene content is 1%, the graphene agglomerates inside, causing its hardness to decrease. However, when the graphene content is 2%, due to the high content of internal graphene, the agglomeration reaches or even exceeds the limit value, reacting with Ti to form TiC, and the hardness of TiC is second only to diamond, so the hardness increases at 2%.

[0020] When 0.5% of carbon nanotubes are mixed into TC4 titanium alloy, the hardness value reaches the highest, indicating that adding a certain amount of carbon nanotubes has a significant effect on the hardness of TC4 titanium alloy. The reason for the hardness enhancement is that the C atoms in the carbon nanotubes are embedded in the matrix, which changes the lattice constant of the surrounding matrix. In addition, some TiC is generated, which hinders the movement of dislocations together with the carbon nanotubes, so that a large number of dislocations are accumulated in the parts where they contact each other, thereby increasing its hardness. As the carbon nanotube content increases from 0.5% to 2%, the hardness of the composite material gradually decreases because the carbon nanotubes are agglomerated, resulting in a decrease in its hardness. Since the specific surface area of ​​carbon nanotubes is larger than that of graphene, the agglomeration amount has not reached the maximum value when the carbon nanotube content is 2%, so the hardness value has been decreasing. However, as the carbon nanotube content continues to increase, the hardness may show a trend of gradual enhancement, because the agglomeration amount of carbon nanotubes will definitely reach the limit value or even exceed the limit value. At this time, a large amount of TiC will be generated, and the carbon nanotubes themselves have a very high hardness, so the hardness enhancement phenomenon will occur.

[0021] Similarly, when boron carbide and silicon carbide nano-reinforcement phases are mixed into TC4 titanium alloy, the hardness of the composite material also shows a trend of first increasing, then decreasing, and then increasing again.

[0022] The hardness of the composite material sintered at 1250℃ is greater than that of the composite material sintered at 1200℃. Because when TC4 titanium alloy and nano-reinforced phase are at 1200℃, the nano-reinforced phase is not completely embedded in the TC4 titanium alloy, and there are still many vacancies that affect its bonding, so the hardness is lower in comparison. At 1250℃, most of the nano-reinforced phase has been embedded in the TC4 titanium alloy, and due to the increase in temperature, the grains are better bonded and there are fewer vacancies. Therefore, the sample sintered at 1250℃ is harder than the sample sintered at 1200℃.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1) The hardness of the traditional TC4 titanium alloy is low, resulting in low wear resistance, which limits the application of TC4 titanium alloy. The present invention adds nano-scale graphene, carbon nanotubes, boron carbide, and silicon carbide particles to the micron-scale TC4 titanium alloy powder, which can effectively improve the hardness of the TC4 titanium alloy.

[0025] 2) The TC4 titanium alloy and the nano-reinforced phase in the composite material of the present invention undergo phase transformation at high temperature to generate a dispersed TiC hard phase, which can effectively improve the hardness of the composite material. For different nano-reinforced phases, the appropriate nano-reinforced phase ratio and sintering temperature are selected to significantly improve the hardness of the TC4 titanium alloy, up to 4000HV.

[0026] 3) The present invention can greatly reduce the porosity of the composite material and improve the bonding degree of TC4 titanium alloy powder by selecting reasonable tableting process parameters and sintering process parameters, thus providing a guarantee for the industrial application of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a scanning electron microscope microstructure image of the TC4 / boron carbide composite material in Example 3 of the present invention, wherein the micron-spherical material is TC4 titanium alloy particles, and the material between the TC4 titanium alloy particles is boron carbide.

[0028] Figure 2 This is a scanning electron microscope microstructure image of the TC4 / silicon carbide composite material in Example 4 of the present invention, wherein the micron-spherical material is TC4 titanium alloy particles, and the material between the TC4 titanium alloy particles is silicon carbide. DETAILED DESCRIPTION

[0029] The specific implementation modes of the present invention are further described below in conjunction with examples. The following examples are used to specifically illustrate the contents of the present invention. These examples are only general descriptions of the contents of the present invention and do not limit the contents of the present invention.

[0030] A method for preparing a nano-reinforced titanium-based composite material, wherein the base material is TC4 titanium alloy powder with an average particle size of 60 to 150 μm; the reinforcing phase is one of nano-graphene, carbon nanotubes, boron carbide nanoparticles, and silicon carbide nanoparticles;

[0031] The preparation method comprises the following steps:

[0032] 1) Using a ball mill to uniformly mix the experimental materials, the mass fraction of the nanoparticles in the mixture is 0.2-2.0 wt%;

[0033] 2) using epoxy resin and latex glue as adhesives to agglomerate the mixed powder obtained in step 1) into a mass, and then placing the mass in a tool steel mold of a tablet press, and completing the tableting of the composite material through the steps of filling-pressing-pressing-holding-demolding;

[0034] 3) Sintering the pressed tablet obtained in step 2) in an argon-protected box-type atmosphere furnace.

[0035] The ball mill has an orbital speed of 100 to 300 r / min, a rotational speed of 300 to 600 r / min, a frequency of 30 to 50 Hz, a required time of 15 to 30 minutes, and a unidirectional operation mode.

[0036] The tableting parameters are as follows: the maximum pressure borne by the mold is 50-450 MPa, and the holding time is 10-60 s;

[0037] The mass of the tablet sample is 6-7 g, the shape of the tablet sample is a disc, the diameter is 20-50 mm, and the thickness is 5-50 mm.

[0038] The sintering parameters are as follows: the sintering heating method is heating with the furnace, and the average heating rate is 5-20°C / min; the sintering temperature is selected to be 1000-1450°C; and the sintering cooling method is furnace cooling.

[0039] Embodiment 1:

[0040] A nano-reinforced TC4 composite material, the matrix material is TC4 titanium alloy powder, the average particle size is 98μm, and the reinforcing phase is nano-scale graphene;

[0041] The nano-enhanced TC4 composite material is prepared by a method comprising the following steps:

[0042] The mass fraction of graphene in the composite material is 2.0%. The experimental materials were uniformly mixed together using a ball mill. The revolution speed of the ball mill was 300r / min, the rotation speed was 600r / min, the frequency was 50Hz, the required time was 30min, and the operation mode was unidirectional. Epoxy resin and milky white glue (ratio of about 3:1) were used as adhesives to condense the powder into a mass. Then the mass was placed in the tool steel mold of the tablet press, and the tableting of the composite material was completed through the steps of filling-pressing-holding-demolding. The maximum pressure borne by the mold was about 100MPa, and the holding time was 30s. The sample mass was 7g, the sample shape was disc-shaped, the sample diameter was 25mm, and the sample thickness was about 5mm. The sample was sintered in an argon-protected box-type atmosphere furnace. The sintering heating method was heating with the furnace, and the average heating rate was 10℃ / min. The sintering temperature was selected to be 1200℃. The sintering cooling method was furnace cooling. The TC4 titanium alloy particles in the TC4 / graphene composite material are tightly connected.

[0043] According to performance testing, the hardness of the nano-reinforced TC4 composite material prepared in this embodiment is 879 HV, which is higher than the hardness of the TC4 titanium alloy of 381 HV.

[0044] Embodiment 2:

[0045] A nano-reinforced TC4 composite material, the matrix material is TC4 titanium alloy powder, the average particle size is 98μm, and the reinforcing phase is carbon nanotubes;

[0046] The nano-enhanced TC4 composite material is prepared by a method comprising the following steps:

[0047] The mass fraction of carbon nanotubes in the composite material is 0.5%. The experimental materials are uniformly mixed together using a ball mill. The revolution speed of the ball mill is 300r / min, the rotation speed is 600r / min, the frequency is 50Hz, the required time is 30min, and the operation mode is unidirectional. Epoxy resin and milky white glue (ratio of about 3:1) are used as adhesives to condense the powder into a mass. Then the mass is placed in the tool steel mold of the tablet press, and the tableting of the composite material is completed through the steps of filling-pressing-holding-demolding. The maximum pressure that the mold withstands is about 100MPa, and the holding time is 30s. The sample mass is 7g, the sample shape is disc-shaped, the sample diameter is 25mm, and the sample thickness is about 5mm. The sample is sintered in an argon-protected box-type atmosphere furnace. The sintering heating method is heating with the furnace, and the average heating rate is 10℃ / min. The sintering temperature is selected to be 1250℃. The sintering cooling method is furnace cooling. The TC4 titanium alloy particles in the TC4 / carbon nanotube composite material are closely connected.

[0048] According to performance testing, the hardness of the nano-reinforced TC4 composite material prepared in this embodiment is 3324 HV, which is higher than the hardness of the TC4 titanium alloy 381 HV.

[0049] Embodiment 3:

[0050] A nano-reinforced TC4 composite material, the matrix material is TC4 titanium alloy powder, the average particle size is 98μm, and the reinforcing phase is boron carbide;

[0051] The nano-enhanced TC4 composite material is prepared by a method comprising the following steps:

[0052] The mass fraction of boron carbide in the composite material is 0.2%. The experimental materials are uniformly mixed together using a ball mill. The revolution speed of the ball mill is 300r / min, the rotation speed is 600r / min, the frequency is 50Hz, the required time is 30min, and the operation mode is unidirectional. Epoxy resin and milky white glue (ratio of about 3:1) are used as adhesives to condense the powder into a mass. Then the mass is placed in the tool steel mold of the tablet press, and the tableting of the composite material is completed through the steps of filling-pressing-holding-demolding. The maximum pressure that the mold withstands is about 100MPa, and the holding time is 30s. The sample mass is 7g, the sample shape is disc-shaped, the sample diameter is 25mm, and the sample thickness is about 5mm. The sample is sintered in an argon-protected box-type atmosphere furnace. The sintering heating method is heating with the furnace, and the average heating rate is 10℃ / min. The sintering temperature is selected to be 1250℃. The sintering cooling method is furnace cooling. The scanning electron microscope micrograph of TC4 / boron carbide composite material is shown in Figure 1 As shown in Figure 2, the TC4 titanium alloy particles in the TC4 / boron carbide composite material are closely connected.

[0053] According to performance testing, the hardness of the nano-reinforced TC4 composite material prepared in this embodiment is 2520 HV, which is higher than the hardness of the TC4 titanium alloy of 381 HV.

[0054] Embodiment 4:

[0055] A nano-reinforced TC4 composite material, the matrix material is TC4 titanium alloy powder, the average particle size is 98μm, and the reinforcing phase is silicon carbide;

[0056] The nano-enhanced TC4 composite material is prepared by a method comprising the following steps:

[0057] The mass fraction of silicon carbide in the composite material is 0.2%. The experimental materials are uniformly mixed together using a ball mill. The revolution speed of the ball mill is 300r / min, the rotation speed is 600r / min, the frequency is 50Hz, the required time is 30min, and the operation mode is unidirectional. Epoxy resin and milky white glue (ratio of about 3:1) are used as adhesives to condense the powder into a mass. Then the mass is placed in the tool steel mold of the tablet press, and the tableting of the composite material is completed through the steps of filling-pressing-holding-demolding. The maximum pressure borne by the mold is about 100MPa, and the holding time is 30s. The sample mass is 7g, the sample shape is disc-shaped, the sample diameter is 25mm, and the sample thickness is about 5mm. The sample is sintered in an argon-protected box atmosphere furnace. The sintering heating method is heating with the furnace, and the average heating rate is 10℃ / min. The sintering temperature is selected to be 1250℃. The sintering cooling method is furnace cooling. The scanning electron microscope micrograph of TC4 / silicon carbide composite material is shown in Figure 2 As shown in Figure 2, the TC4 titanium alloy particles in the TC4 / silicon carbide composite material are closely connected.

[0058] According to performance testing, the hardness of the nano-reinforced TC4 composite material prepared in this embodiment is 4058 HV, which is higher than the hardness of the TC4 titanium alloy of 381 HV.

[0059] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0060] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a nano-reinforced titanium-based composite material, characterized in that: The base material is TC4 titanium alloy powder with an average particle size of 60 to 150 μm; the reinforcing phase is one of nano-graphene, carbon nanotubes, boron carbide nanoparticles, and silicon carbide nanoparticles; The preparation method comprises the following steps: 1) using a ball mill to uniformly mix the materials, wherein the mass fraction of the nanoparticles in the mixture is 0.2 to 2.0 wt %; 2) using epoxy resin and latex glue as adhesives to agglomerate the mixed powder obtained in step 1) into a mass, and then placing the mass in a tablet press to complete tableting of the composite material; 3) Sintering the pressed tablet obtained in step 2) in an argon-protected box-type atmosphere furnace.

2. The method for preparing a nano-reinforced titanium-based composite material according to claim 1, characterized in that: The ball mill has an orbital speed of 100 to 300 r / min, a rotational speed of 300 to 600 r / min, a frequency of 30 to 50 Hz, a required time of 15 to 30 minutes, and a unidirectional operation mode.

3. The method for preparing a nano-reinforced titanium-based composite material according to claim 1, characterized in that: The tabletting parameters are as follows: the maximum pressure borne by the mold is 50 to 450 MPa, and the pressure holding time is 10 to 60 seconds.

4. The method for preparing a nano-reinforced titanium-based composite material according to claim 1 or 3, characterized in that: The mass of the tablet sample is 6-7 g, the shape of the tablet sample is a disc, the diameter is 20-50 mm, and the thickness is 5-50 mm.

5. The method for preparing a nano-reinforced titanium-based composite material according to claim 1, characterized in that: The sintering parameters are as follows: the sintering heating method is heating with the furnace, and the average heating rate is 5-20°C / min; the sintering temperature is selected to be 1000-1450°C; and the sintering cooling method is furnace cooling.